Comparative Analysis of the Effect of Different Types of Green Roofs over the Linear Thermal Bridges. Issue 1 (September 2020) - Baciu, I-R; Isopescu, D N; Taranu, N; Lupu, M L; Maxineasa, S G
Abstract: During recent years, it appears in the background of global discussions the negative impact resulted from the daily humans' activities. Taking into account the present surface of the built environment and also the fact that this area will significantly increase shortly, it can be considered that using the buildings to develop new solutions like green roofs. The expanding benefits of a green roof emphasize the key role of this structure in the overall thermal performance of buildings and microclimate conditions of indoor spaces. The main objective of the study is to analyse and to interpret the influence of all three main categories of a green roof on the heat flow, in the thermal bridges developed structurally in buildings. The study based on the structural elements of each type of roof, their thermic characteristics and the principal types of thermal bridges will represent a comparison between the thermal impact of a classical terrace roof and that of the extensive, semi-intensive and intensive green roof. In conclusion, the unpredictable results obtained for the analysed thermal parameters let conclude that the green roof solution in all the three forms has an environmental impact, in terms of both sustainability and aesthetics.